Evaluation of the gas emissions during the thermochemical conversion of eucalyptus woodchips - Silva, João (2022)
The combustion of solid biomass in industrial boilers involves a sequence of processes that include heating, drying, devolatilization, and char conversion. To maintain a repeatable and fully controlled environment, and to monitor all the dynamics involved in the phenomena at a real scale, field-scale experiments become necessary to perform investigations. In this way, to evaluate different thermochemical conversion conditions of biomass particles under an oxidative atmosphere, and to quantify the emission of the main gas compounds continuously, a small-scale reactor was developed and presented in this paper. Hence, in this work, larger particles of eucalyptus are burned at 400 and 800 °C under different stoichiometric conditions to understand the differences between different biomass conversion regimes (gasification and combustion). The analysis of the mass loss at the different temperatures was characterized by only two different and consecutive stages for both thermochemical conditions. The first region does not present the influence on the air flow rate; however, there is a significant difference in the second region. This fact highlighted the importance of the diffusion of oxygen during the char conversion. Regarding the quantification of the gas compounds, an increase of around 3 times in the CO and CO2 emissions when gasification occurs was observed at 400 °C. However, at 800 °C, the same trend was verified, also verifying a considerable amount of CH4.